PENGGUNAAN BAHASA INGGRIS SEBAGAI STRATEGI KOMUNIKASI GLOBAL DALAM INDUSTRI PARIWISATA - Nabila Syafitri; Fitri Annisa; Eko Purnomo; Muhammad Lutfi; Suhairi Suhairi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The more advanced the development of technology, the more likely it is that something can be searched for and known. It's the same as finding out about vacation spots and relaxing while enjoying your time. So with this convenience, one of the things that is affected is the tourism industry sector. The tourism industry in Indonesia is currently developing rapidly. Indonesian tourism is currently considered Indonesia's core business by the World Bank. With so many tourists present as tourism objects, this development must be in line with the competence and skills of the people involved in this industry, especially English language skills, for the good and sustainability as well as the special attraction of the tourist spot. The aim of this research is to find out "The Use of English as a Global Communication Strategy in the Tourism Industry". This research uses qualitative methods with observations and interviews and from several scientific journals relevant to this topic. The results of this research are that English has a very important role in the communication process that occurs in the tourism industry, both communication between tourism actors and tourists and communication in business and economic matters.